Euro-Par 2010 - Parallel Processing 16th International Euro-Par Conference, Ischia, Italy, August 31 - September 3, 2010, Proceedings, Part II - D$1 (BAmbra, Pasqua.s; Guarracino, Mario; Talia, Domenico; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 16th International Euro-Par Conference held in Ischia, Italy, in August/September 2010. The 90 revised full papers presented were carefully reviewed and selected from 256 submissions. The papers are organized in topical sections on support tools and environments; performance prediction and evaluation; scheduling and load-balancing; high performance architectures and compilers; parallel and distributed data management; grid, cluster and cloud computing; peer to peer computing; distributed systems and algorithms; parallel and distributed programming; parallel numerical algorithms; multicore and manycore programming; theory and algorithms for parallel computation; high performance networks; and mobile and ubiquitous computing.
Topic 9: Parallel and Distributed Programming -- Parallel and Distributed Programming -- Transactional Mutex Locks -- Exceptions for Algorithmic Skeletons -- Generators-of-Generators Library with Optimization Capabilities in Fortress -- User Transparent Task Parallel Multimedia Content Analysis -- Parallel Simulation for Parameter Estimation of Optical Tissue Properties -- Topic 10: Parallel Numerical Algorithms -- Parallel Numerical Algorithms -- Scalability and Locality of Extrapolation Methods for Distributed-Memory Architectures -- CFD Parallel Simulation Using Getfem++ and Mumps -- Aggregation AMG for Distributed Systems Suffering from Large Message Numbers -- A Parallel Implementation of the Jacobi-Davidson Eigensolver and Its Application in a Plasma Turbulence Code -- Scheduling Parallel Eigenvalue Computations in a Quantum Chemistry Code -- Scalable Parallelization Strategies to Accelerate NuFFT Data Translation on Multicores -- Topic 11: Multicore and Manycore Programming -- Multicore and Manycore Programming -- JavaSymphony: A Programming and Execution Environment for Parallel and Distributed Many-Core Architectures -- Scalable Producer-Consumer Pools Based on Elimination-Diffraction Trees -- Productivity and Performance: Improving Consumability of Hardware Transactional Memory through a Real-World Case Study -- Exploiting Fine-Grained Parallelism on Cell Processors -- Optimized On-Chip-Pipelined Mergesort on the Cell/B.E. -- Near-Optimal Placement of MPI Processes on Hierarchical NUMA Architectures -- Parallel Enumeration of Shortest Lattice Vectors -- A Parallel GPU Algorithm for Mutual Information Based 3D Nonrigid Image Registration -- Multi-GPU and Multi-CPU Parallelization for Interactive Physics Simulations -- Long DNA Sequence Comparison on Multicore Architectures -- Adaptive Fault Tolerance for Many-Core Based Space-Borne Computing -- Maestro: Data Orchestration and Tuning for OpenCL Devices -- Multithreaded Geant4: Semi-automatic Transformation into Scalable Thread-Parallel Software -- Parallel Exact Time Series Motif Discovery -- Optimized Dense Matrix Multiplication on a Many-Core Architecture -- A Language-Based Tuning Mechanism for Task and Pipeline Parallelism -- A Study of a Software Cache Implementation of the OpenMP Memory Model for Multicore and Manycore Architectures -- Programming CUDA-Based GPUs to Simulate Two-Layer Shallow Water Flows -- Topic 12: Theory and Algorithms for Parallel Computation -- Theory and Algorithms for Parallel Computation -- Analysis of Multi-Organization Scheduling Algorithms -- Area-Maximizing Schedules for Series-Parallel DAGs -- Parallel Selection by Regular Sampling -- Ants in Parking Lots -- Topic 13: High Performance Networks -- High Performance Networks -- An Efficient Strategy for Reducing Head-of-Line Blocking in Fat-Trees -- A First Approach to King Topologies for On-Chip Networks -- Optimizing Matrix Transpose on Torus Interconnects -- Topic 14: Mobile and Ubiquitous Computing -- Mobile and Ubiquitous Computing -- cTrust: Trust Aggregation in Cyclic Mobile Ad Hoc Networks -- Maximizing Growth Codes Utility in Large-Scale Wireless Sensor Networks -- @Flood: Auto-Tunable Flooding for Wireless Ad Hoc Networks -- On Deploying Tree Structured Agent Applications in Networked Embedded Systems -- Meaningful Metrics for Evaluating Eventual Consistency -- Caching Dynamic Information in Vehicular Ad Hoc Networks -- Collaborative Cellular-Based Location System.
Keywords: Computer science; Operating systems (Computers).; Computer system performance; Computer software; Electronic data processing; Computer Science; System Performance and Evaluation; Algorithm Analysis and Problem Complexity; Programming Techniques; Numeric Computing; Processor Architectures; Performance and Reliability